How to site grassed areas to reduce agricultural erosion efficiently? A computational analysis in Finland - Tähtikarhu, Mika; Räsänen, Timo A.; Uusi-Kämppä, Jaana; Hyväluoma, Jari (Elsevier, 2025)
Spatial patterns of land-cover and agricultural operations have clear impacts on soil erosion. Allocating a portion of cultivated area for grass is a widely applied strategy to control erosion. However, it is still unclear how much and where grassed area should be spatially targeted in different landscapes to control erosion efficiently. To address this challenge, we estimate the potential of high-resolution RUSLE-based spatial targeting of grassed areas to improve erosion mitigation in two topographically different catchments in southern Finland. Erosion reductions of 1) policy-based targeting (buffer strips along main streams according to current CAP strategy) were compared with 2) RUSLE-targeted grassed areas (based on the highest computed erosion values within field parcels and sub-catchments). Furthermore, we computationally explored 3) how different rates of optimally located grass areas affected erosion and 4) how the areas could be computationally processed to continuous entities. The erosion reductions were estimated with 2 × 2 m2 resolution RUSLE computations in all the scenarios. The RUSLE-targeted grassed areas demonstrated greater erosion reductions compared to the policy-based siting of grass areas along riparian fields. With optimal targeting, erosion risks could potentially be reduced up to 24 percentage points (up to 46 % erosion reduction), compared to the buffer strips. Increasing optimally targeted grassed area gradually from 0 to 100 % decreased erosion non-linearly. The largest share of erosion was generated in disproportionally small land areas (∼20 % of the land area). The location of the hotspots in relation to the streams varied between the sub-catchments and field parcels. These quantifications demonstrate the potential value of models for targeted landscape scale spatial erosion management. A more comprehensive assessment of erosion mitigation could benefit of improved empirical validation and consideration of other aspects of erosion and sediment transport, such as local drainage efficiency and reduction of erosion during flooding of rivers.
Keywords: erosion; RUSLE; erosion control; targeting; siting